Community-Led Health Initiatives for Torres Straits Island Communities in a Changing Climate: Implementing Core Values for Mitigation and Adaptation - Nina Lansbury; Andrew M. Redmond; Francis Nona (International Journal of Environmental Research and Public Health, 2022)
First Nations Peoples have a long history of living in Australia’s changing climate and a deep knowledge of their traditional estate (‘Country’). However, human-induced climate change raises unforeseen risks to the health of First Nations Peoples—especially in remotely located communities. This includes the Torres Strait Islands, where a local leader asked our Torres Strait Islander co-author, ’We know that you will return to your Country—unlike previous researchers. So how can you help with climate change?’ In response, this research describes four core values focused on supporting First Nations Peoples’ health and wellbeing: co-design, appropriate governance, support for self-determination, and respectfully incorporating Indigenous Knowledges into health-protective climate initiatives. Supporting the health and wellbeing of Torres Strait Islanders to continue living in the remote Torres Strait Islands in a changing climate can enable long-term care for Country, maintenance of culture, and a sense of identity for First Nations Peoples. Ensuring these core values are implemented can support the health of present and future generations and will likely be applicable to other First Nations communities.